2018
DOI: 10.4269/ajtmh.17-1004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Treatment Coverage and Enhanced Mass Drug Administration for Onchocerciasis and Lymphatic Filariasis in Five Local Government Areas Treating Twice Per Year in Edo State, Nigeria

Abstract: The western region of Edo state in southern Nigeria is highly endemic for onchocerciasis. Despite years of mass drug administration (MDA) with ivermectin (IVM), reports suggest persistently high prevalence of onchocerciasis, presumably because of poor coverage. In 2016, twice-per-year treatment with IVM (combined with albendazole for lymphatic filariasis in the first round where needed) began in five local government areas (LGAs) of Edo state. We undertook a multistage cluster survey within 3 months after each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…In contrast, MDA for onchocerciasis treatment in Nigeria Edo state in 2016 reported that most of the respondents were not offered IVM. 17 …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, MDA for onchocerciasis treatment in Nigeria Edo state in 2016 reported that most of the respondents were not offered IVM. 17 …”
Section: Discussionmentioning
confidence: 99%
“…More sensitive diagnostics are imperative in the era of successfully implemented NTD control programmes because microscopy-based tests are not sufficiently sensitive to detect residual infection. This may have accounted for the lack of microbiological confirmation in some of the cases of onchodermatitis and lymphatic filariasis seen in this location as MDA directed programmes have been implemented to control both diseases in surrounding areas (31).…”
Section: Microbiological Analysismentioning
confidence: 98%
“…Hotez et al described Nigeria as "ground zero" for NTDs because of the high prevalence of these diseases in the country (30). Specifically, Edo state where the study site is located is highly endemic for onchocerciasis (31). In the ensuing years since the London declaration on NTDs in 2012, giant strides have been made in the control of NTDs with chemotherapy reaching a billion people in 2014.…”
Section: Microbiological Analysismentioning
confidence: 99%
“…Regular treatments with broad-spectrum antihelminth drugs (such as the benzimidazoles, mebendazole, or albendazole) are effective at reducing morbidity from STH infections and are well-tolerated, while ivermectin has been employed in areas endemic for filarial diseases. In the case of ivermectin treatment of filariasis in Africa, while progress is being made (e.g., a recent report from Sierra Leone described reductions in Onchocerca worm burden [16]), in other countries and areas issues such as poor medicine distribution (e.g., one study in Nigeria [17]) and treatment side effects (e.g, increased epilepsy cases in Tanzania [18]) also need to be addressed if elimination of these debilitating parasites is to be achieved. Even so, a meta-analysis of helminth re-infection studies has shown that prevalence can be quick to re-establish-in this case Ascaris, Trichuris, and hookworms re-established over the ensuing 12 months to 94%, 82%, and 57% of pretreatment levels, respectively [19].…”
Section: The Burden Of Helminth Infection In Africamentioning
confidence: 99%